Biomedical Image Registration 5th International Workshop, WBIR 2012, Nashville, TN, USA, July 7-8, 2012, Proceedings - Dawant, Benoit; Christensen, Gary E.; Fitzpatrick, J. Michael; Rueckert, Daniel (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2012)
This book constitutes the refereed proceedings of the 5th International Workshop on Biomedical Image Registration, WBIR 2012, held in Nashville, Tennessee, USA, in July 2012. The 20 full papers and 11 poster papers included in this volume were carefully reviewed and selected from 44 submitted papers. They full papers are organized in the following topical sections: multiple image sets; brain; non-rigid anatomy; and frameworks and similarity measures.